Human oral mucosa cell atlas reveals a stromal-neutrophil axis regulating tissue immunity - Williams, Drake Winslow; Greenwell-Wild, Teresa; Brenchley, Laurie; Dutzan, Nicolas; Overmiller, Andrew; Sawaya, Andrew Phillip; Webb, Simone; Martin, Daniel; Hajishengallis, George; Divaris, Kimon; Morasso, Maria; Haniffa, Muzlifah; et al. (Cell, 2021)
The oral mucosa remains an understudied barrier tissue. This is a site of rich exposure to antigens and commensals, and a tissue susceptible to one of the most prevalent human inflammatory diseases, periodontitis. To aid in understanding tissue-specific pathophysiology, we compile a single-cell transcriptome atlas of human oral mucosa in healthy individuals and patients with periodontitis. We uncover the complex cellular landscape of oral mucosal tissues and identify epithelial and stromal cell populations with inflammatory signatures that promote antimicrobial defenses and neutrophil recruitment. Our findings link exaggerated stromal cell responsiveness with enhanced neutrophil and leukocyte infiltration in periodontitis. Our work provides a resource characterizing the role of tissue stroma in regulating mucosal tissue homeostasis and disease pathogenesis.